2021
DOI: 10.33590/emj/21-000951
|View full text |Cite
|
Sign up to set email alerts
|

Cannabinoids in the Treatment of Epilepsy: A Review

Abstract: Cannabinoids have been studied for their role in the treatment of epilepsy for many years. The U.S. Food and Drug Administration (FDA) approved them for the treatment of some refractory syndromes in 2018. Cannabidiol and tetrahydrocannabinol are the most commonly studied cannabinoids and have been studied in great depth vis-à-vis their pharmacokinetics and pharmacodynamics. Studies have shown the efficacy of cannabinoids in the treatment of refractory epilepsy. A substantial amount of research has been perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Several randomized, placebo-controlled clinical trials and retrospective studies conducted on patients with refractory epilepsy and genetic syndromes support evidence from preclinical studies and strongly indicate that CBD can reduce seizure frequency [12,67,68,[72][73][74][75][76][77][78]. The Food and Drug Administration in the USA has already approved cannabinoids for the treatment of several treatment-resistant epilepsy syndromes [68,78]. Medical cannabis, especially CBD--based therapy, could become an important addition to conventional anticonvulsive drugs used in refractory epilepsy both in children and adults as it significantly reduces seizure frequency, improves patients' quality of life and sleep patterns and does not cause severe side effects [71,79].…”
Section: Epilepsymentioning
confidence: 82%
See 2 more Smart Citations
“…Several randomized, placebo-controlled clinical trials and retrospective studies conducted on patients with refractory epilepsy and genetic syndromes support evidence from preclinical studies and strongly indicate that CBD can reduce seizure frequency [12,67,68,[72][73][74][75][76][77][78]. The Food and Drug Administration in the USA has already approved cannabinoids for the treatment of several treatment-resistant epilepsy syndromes [68,78]. Medical cannabis, especially CBD--based therapy, could become an important addition to conventional anticonvulsive drugs used in refractory epilepsy both in children and adults as it significantly reduces seizure frequency, improves patients' quality of life and sleep patterns and does not cause severe side effects [71,79].…”
Section: Epilepsymentioning
confidence: 82%
“…Several randomized, placebo-controlled clinical trials and retrospective studies conducted on patients with refractory epilepsy and genetic syndromes support evidence from preclinical studies and strongly indicate that CBD can reduce seizure frequency [12,67,68,[72][73][74][75][76][77][78]. The Food and Drug Administration in the USA has already approved cannabinoids for the treatment of several treatment-resistant epilepsy syndromes [68,78].…”
Section: Epilepsymentioning
confidence: 86%
See 1 more Smart Citation
“…Systematic reviews have concluded that cannabinoids show limited efficacy as a monotherapy in reducing non-cancer pain [26][27][28][29][30][31][32][33], treating mental illnesses [34][35][36][37][38], and treating epilepsy [33,39,40] (with the exception of treating drug-resistant epilepsy for which there is strong evidence [14,15]), with modest improvements at best. Other systematic reviews conducted by the TGA have found that currently there is some evidence of efficacy for both THC and CBD in treatment of chronic non-cancer related pain [18] and neuropathic pain [41] (although both tend to favour THC-containing products).…”
Section: Plos Onementioning
confidence: 99%